Particle size segregation in granular pipe flow - Müller, Patric; Panchenko, Artem; Ku, Wing To; Pöschel, Thorsten (Chaos, 2025)
The flow of granular material through pipes is characterized by significant variations in solid fraction (density waves) along the pipe. Previously, it has been shown that this intermittent flow behavior can be mitigated by adding a texture to the pipe’s inner wall. This work shows that adding surface roughness can lead to particle size segregation as a side effect in bidisperse systems. Using particle simulations, we characterize the parameter ranges in which segregation occurs.
CRIS-Team Scopus Importer:2025-05-02